Charge transfer events in semiconducting single-wall carbon nanotubes - Oelsner, Christian; Antonia Herrero, M.; Ehli, Christian; Prato, Maurizio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2011)
Electron-donating ferrocene units have been attached to SWNTs, with different degrees of functionalization. By means of a complementary series of novel spectroscopic techniques (i.e., steady-state and time-resolved), we have documented that mutual interactions between semiconducting SWNT and the covalently attached electron donor (i.e., ferrocene) lead, in the event of photoexcitation, to the formation of radical ion pairs. In the accordingly formed radical ion pairs, oxidation of ferrocene and reduction of SWNT were confirmed by spectroelectrochemistry. It is, however, shown that only a few semiconducting SWNTs [i.e., (9,4), (8,6), (8,7), and (9,7)] are susceptible to photoinduced electron transfer processes. These results are of relevant importance for the development of SWNT-based photovoltaics. © 2011 American Chemical Society.